Kajian Literatur: Strategi Komunikasi untuk Sosialisasi Pemberian Terapi Pencegahan Tuberkulosis (TPT) - Miratul Hasanah (JURNAL PENDIDIKAN KESEHATAN, 2025)
Tuberculosis Preventive Treatment (TPT) is a strategy to prevent the spread of tuberculosis (TB), particularly among high-risk populations. However, TPT coverage in Indonesia remains far below national targets. Effective communication has an essential role in increasing knowledge, acceptance and adherence of the population to TPT. This literature review aims to identify communication strategies used to promote acceptance of TPT. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) was used for conducting the study. The literature was retrieved through Google Scholar using Bahasa Indonesia and English keywords. Articles which original research, published within 10 years, relevant to the topic and fully access were selected and synthesized. Thirteen studies met the criteria and were categorized into personal, group and public communication models. The personal communication strategy was effective in increasing knowledge and improving adherence. This model such as counseling, home visits, education using videos, leaflets, booklets and reminder messages. Group communication strategies utilized flipcharts, booklets, presentations and short films suitable to increase awareness of TB risks, TB screening and TPT. Public campaigns through radio and television, as well as opening a health booth in public spaces, were a public communication strategy that aimed to improve public awareness. Each communication strategy is suitable for specific objectives and a target audience. This review provides insight from multiple countries; it may not fully represent the current Indonesia condition.